Malaysia's counter - measures against maritime piracy and armed robbery in the straits of Malacca, 2001-2010 - Noridah binti Bahrin (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2012)
This study analyzes Malaysia's counter-measures against piracy and armed robbery upon ships in the Straits of Malacca (SOM) from 2001-2010 through the mechanisms of state-sponsored naval forces, regional intelligence sharing, surveillance radar, the court system and land-based operations. The strengths and challenges of these counter-measures are examined in order to come up with suggestions for future plans in developing the counter-measures. In addition, this study also examines the nature of pirate attacks and armed robbery and evaluates Malaysia's capability to safeguard the SOM from any types of crimes. Data were gathered through various sources such as the annual reports of government agencies and non-governmental organizations, international conference papers and in-depth personal interviews of representatives from the Maritime Institute of Malaysia (MIMA), Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia (IIUM), Marine Operation Force (MOF) of the Royal Malaysian Police, the National Security Council (NSC), the Marine Department Peninsular Malaysia (MarDep) and the Malaysian Maritime Enforcement Agency (MMEA). This study finds that Malaysia uses the mechanisms of state-sponsored naval forces, regional intelligence sharing, the court system and surveillance radars as counter-measures against pirate attacks and armed robbery upon ships in the SOM, 2001-2010.